Imagens da imigração europeia nas pinturas de Pedro Weingärtner: representação do imigrante e do processo de colonização (século XIX e XX) - Fochesatto, Cyanna Missaglia de (Universidade do Vale do Rio dos Sinos, 2015)
This study aims to to analyze some paintings from the gaucho artist Pedro Weingärtner, a regional theme that address the representation of the European immigrant and the colonization process in Rio Grande do Sul, from the period of the nineteenth and early twentieth centuries. The analysis of these paintings was made through the understanding of memory and biography of its creator, so that it was possible to understand the type of identity of the immigrant present in the paintings. It was intended to deeply understand how this social type was represented in the paintings, their characteristics, their way of life, the gaps of sociability and work, the landscapes and socio-cultural elements. The relevance of this research is given by the absence of a major study on Pedro Weingärtner and also for the contribution in the field of studies of history and of images, once it contributes - in an interdisciplinary way - with studies about German immigration, pictures and fine arts. It was found throughout the research the representation of an immigrant strongly allied to rural areas and work on the land, seeking the construction of the image of a social type that is both a worker in the countryside as the main causative agent of transformation of the natural landscape Brazilian.
Keywords: Pedro Weingärtner; Imigração alemã; Imagens; Paisagens; Identidade; German immigration; Images; Landscapes; Identity; ACCNPQ::Ciências Humanas::História